Inovasi Digitalisasi Promosi Produk Usaha Masyarakat Berbasis Website Di Medan Denai (PT. Medania Raya Sejahtera) - Hidayah, Nurul; Nurbaiti, Nurbaiti; Aslami, Nuri (Jurnal Manajemen Akuntansi (JUMSI), 2023)
This study aims to analyze the innovation of digital promotion on public business products by using the website of the company PT. Medania Raya Sejahtera. This study is a field study using a qualitative approach; primary and secondary data sources are used, and data collection procedures include interviews, observations, and documentation. The subject in this study is an informant trader company employees PT. Medania Raya Sejahtera. The focus of this study is how to innovate the promotion of community business products by digital means using the website in the company of PT. Medania Raya Sejahtera. The results of this study indicate that in conducting marketing activities, the company PT. Medania Raya Sejahtera has been using the web to improve the effectiveness of marketing activities, especially promotions. With the existence of the web has expanded the company's marketing, because the company's products are better known in various regions, even abroad.